Systematic Review of Research on Pedagogical Content Knowledge in Mathematics: Insights from a Topic-Specific Approach - Grigaliūnienė, Monika; Lehtinen, Erno; Verschaffel, Lieven; Depaepe, Fien (Springer Science and Business Media LLC, 2025)
One of the most important characteristics of mathematics teachers is their knowledge enabling them to provide learning experiences that promote students’ understanding, defined as pedagogical content knowledge by Shulman in 1986. In recent decades, the number of studies on mathematics teachers’ pedagogical content knowledge has steadily increased. The current review captures the results of 237 studies published in the last ten years (2013-2022), thematically addressing two components included in all definitions of pedagogical content knowledge - knowledge of instructional strategies and representations and knowledge of student learning difficulties. We approach this review from a topic-specific perspective presenting results of PCK research on nine mathematical topics, the most research relating to rational numbers, geometry and algebra. Altogether 83 unique topic-specific learning difficulties were mentioned in PCK measures including procedural and conceptual difficulties or combinations of them. Teaching strategies were reported less frequently and some strategies such as the use of manipulatives and visualizations were mentioned in relation to many mathematical topics.